The Ephrin receptor EphA4 restricts axonal sprouting and enhances branching in the injured mouse optic nerve. (12th July 2014) - Joly, Sandrine; Jordi, Noémie; Schwab, Martin E.; Pernet, Vincent
Abstract The lack of axonal regeneration in the adult central nervous system is in part attributable to the presence of inhibitory molecules present in the environment of injured axons such as the myelin‐associated proteins Nogo‐A and MAG and the repulsive guidance molecules Ephrins, Netrins and Semaphorins. In the present study, we hypothesized that EphA4 and one of its potential binding partners EphrinA3 may participate in the inhibition of adult axon regeneration in the model of adult mouse optic nerve injury. Axonal regeneration was analysed in three dimensions after tissue clearing of EphA4 knockout (KO), EphrinA3 KO and wild‐type (WT) optic nerves. By immunohistochemistry, EphA4 was highly expressed in Müller glia endfeet in the retina and in astrocytes in the retina and the optic nerve, while EphrinA3 was present in retinal ganglion cells and oligodendrocytes. Optic nerve crush did not cause expression changes. Significantly more axons grew in the crushed optic nerve of EphA4 KO mice than in WT or EphrinA3 KO animals. Single axon analysis revealed that EphA4 KO axons were less prone to form aberrant branching than axons in the other mouse groups. The expression of growth‐associated proteins Sprr1a and Gap‐43 did not vary between EphA4 KO and WT retinae. However, glial fibrillary acidic protein‐expressing astrocytes were withdrawn from the perilesional area in EphA4 KO, suggesting that gliosis down‐regulation may locally contribute to improve axonal growth at the injury site. In summary, our three‐dimensional analysis of injured mouse optic nerves reveals beneficial effects of EphA4 ablation on the intensity and the pattern of optic nerve axon regeneration.